H3K36 Methylation in Neural Development and Associated Diseases - Zaghi, Mattia; Broccoli, Vania; Sessa, Alessandro (Frontiers in Genetics, 2020)
Post-translational methylation of H3 lysine 36 (H3K36) is an important epigenetic marker that majorly contributes to the functionality of the chromatin. This mark is interpreted by the cell in several crucial biological processes including gene transcription and DNA methylation. The homeostasis of H3K36 methylation is finely regulated by different enzyme classes which, when impaired, lead to a plethora of diseases; ranging from multi-organ syndromes to cancer, to pure neurological diseases often associated with brain development. This mini-review summarizes current knowledge on these important epigenetic signals with emphasis on the molecular mechanisms that (i) regulate their abundance, (ii) are influenced by H3K36 methylation, and (iii) the associated diseases.